2003
DOI: 10.1590/s1516-35982003000400017
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de óleo e adição de complexo enzimático na ração de frangos de corte

Abstract: RESUMO -Dois experimentos foram conduzidos para avaliar o efeito da adição de óleo de soja e de um complexo enzimático em rações à base de milho e farelo de soja, sobre o desempenho de frangos de corte e a digestibilidade dos nutrientes. No experimento 1, foram utilizados 960 pintos de corte, não sexados, os quais receberam os tratamentos em esquema fatorial 4 x 2 (quatro níveis de inclusão de óleo de soja: 0; 2,5; 5,0 e 7,5%, com ou sem adição de um complexo enzimático contendo amilase, xilanase e protease), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 6 publications
(5 reference statements)
2
8
0
6
Order By: Relevance
“…Pucci et al (2003) also did not find significant effect of higher oil inclusion in the feed on dry matter digestibility, when feed intake and excreta were corrected after kaolin withdrawal. On the other hand, Bonnet et al (1997) e Vieira et al (2002) observed a reduction in dry matter digestibility in birds fed diets containing higher fat levels.…”
Section: Diet Had No Influence On Carcass Yieldmentioning
confidence: 68%
See 1 more Smart Citation
“…Pucci et al (2003) also did not find significant effect of higher oil inclusion in the feed on dry matter digestibility, when feed intake and excreta were corrected after kaolin withdrawal. On the other hand, Bonnet et al (1997) e Vieira et al (2002) observed a reduction in dry matter digestibility in birds fed diets containing higher fat levels.…”
Section: Diet Had No Influence On Carcass Yieldmentioning
confidence: 68%
“…Apparent digestibility was measured by total excreta collection, four days weekly, for three weeks. Birds were submitted to six hours to the summer diet was discounted from feed intake and excreta for digestibility calculation, as recommended by Pucci et al (2003).…”
Section: Methodsmentioning
confidence: 99%
“…Os machos apresentaram consumo de ração 4,5% superior em relação às fêmeas. Pucci (2001) verificou que o consumo de ração apresentou comportamento linear crescente com a adição de níveis crescentes de óleo nas rações. Quando se aumentou a inclusão do resíduo da própolis nas rações, aumentaram-se também os ní-veis de óleo para que as rações fossem todas isoenergéticas.…”
Section: Consumo De Raçãounclassified
“…O aumento no consumo de ração nessa fase pode ser explicado pelo aumento crescente de óleo nas rações, o que também foi verificado por Pucci (2001).…”
Section: Ganho De Pesounclassified
“…The inclusion of fats in feeds positively influences broiler performance (Vieira et al, 2002;Pucci et al, 2003), and enhances feed palatability (NRC, 1994). The composition of the fatty acids added to diets affects body fat composition in broilers (Waldroup & Waldroup, 2005), and therefore body fat growth pattern can be modified by dietary fat (Crespo & Esteve-Garcia, 2002).…”
Section: Introductionmentioning
confidence: 99%